829. TSUGA CHINENSIS: Pinaceae. (22nd April 2016) - Aiello, Anthony S.
Summary: Tsuga chinensis Franch. is described and illustrated here and details of its distribution and habitat are also provided. Its history in cultivation and its resistance to the woolly adelgid, ( Adelges tsugae ) which is so damaging to T. canadensis in North America, are discussed.